A stochastic optimization approach for dynamic adaptive scalable video streaming over NDN - Xiangyang Wu; Xiaobin Tan; Yunfeng Shao; Jiawei Ni; Jin Zhu (Chinese Control Conference, 2017)
Named Data Networking (NDN) is a general proposed network layer protocol which offers a set of rich functionality: in-network storage, multi-path forwarding, and data-centric security. The cache and multi-path feature improves the efficiency of transmission but increases the difficulty of the bandwidth estimation. In this paper, a dynamic layer switching strategy using Lyapunov Optimization is proposed for dynamic adaptive scalable video streaming over NDN. It aims for optimizing long-term quality-of-experience(QoE) of users via maximizing video quality subject to a constraint on playback smoothness, interruption and fluctuation. The proposed algorithm does not require a priori knowledge of the network bandwidth dynamics, and is capable of operating online with the client's currently available information. Experimental results indicate that our algorithm performs better than others in NDN.